What is a Forest? An Analysis of the Forest (Conservation) Act - Bahuguna, N. C. (Indian Forester, 2004)
A lot of confusion prevails over the definition of forest. Attempts to define the word ’forest’ applicable in all conditions have not yielded any result. In reference to Forest (Conservation) Act, 1980, the Apex Court has interpreted that in addition to recorded forest, a forest must also be understood by its dictionary meaning. For a meaningful application of this Act, all lands, whether covered with trees or not ifsignificant ecologically, must come under the meaning of forest. Simultaneously, plantation raised by people on their land under social forestry schemes should be excluded under the Act.